2016
DOI: 10.1111/pai.12642
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell epitope‐containing hypoallergenic β‐lactoglobulin for oral immunotherapy in milk allergy

Abstract: Chymotrypsin activity inhibited the formation of βLg in the trypsin hydrolysate of βLg. This βLg trypsin hydrolysate is a novel candidate for peptide-based OIT in cow's milk allergy for safely inducing desensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…There has been evidence in milk allergy that hydrolyzed b-Lactoglobulin (bLg) contains the necessary T cell epitope needed to be a novel candidate for peptide based oral immunotherapy. 50 A recent pilot study evaluated oral immunotherapy with hydrolysed egg in children. 51 Although a 6-month treatment course in a small number of patients was not enough to demonstrate a statistically significant difference in the proportion of patients who became tolerant to egg, they found that patients treated with hydrolysed egg demonstrated increased specific IgG4 and decreased basophil activation as compared to patients treated with placebo, suggesting a trend toward tolerance.…”
Section: Peptide Immunotherapymentioning
confidence: 99%
“…There has been evidence in milk allergy that hydrolyzed b-Lactoglobulin (bLg) contains the necessary T cell epitope needed to be a novel candidate for peptide based oral immunotherapy. 50 A recent pilot study evaluated oral immunotherapy with hydrolysed egg in children. 51 Although a 6-month treatment course in a small number of patients was not enough to demonstrate a statistically significant difference in the proportion of patients who became tolerant to egg, they found that patients treated with hydrolysed egg demonstrated increased specific IgG4 and decreased basophil activation as compared to patients treated with placebo, suggesting a trend toward tolerance.…”
Section: Peptide Immunotherapymentioning
confidence: 99%
“…Chymotrypsin affected the retention of the T‐cell epitope of ßLg when preparing ßLg hydrolysates using food‐grade trypsin. Chymotrypsin activity inhibited the formation of ßLg102‐124 in the trypsin hydrolysate of ßLg, showing that it is a novel candidate for peptide‐based CMA OIT . However, immediate hypersensitivity to extensively hydrolyzed formulas can be observed …”
Section: Cow's Milk Allergymentioning
confidence: 99%
“…Chymotrypsin activity inhibited the formation of ßLg102-124 in the trypsin hydrolysate of ßLg, showing that it is a novel candidate for peptide-based CMA OIT. 16 However, immediate hypersensitivity to extensively hydrolyzed formulas can be observed. 17 Breastfeeding may induce allergic sensitization to peanut.…”
Section: Cow's Milk Allergymentioning
confidence: 99%
“…Oral allergen-specific immunotherapy (oral-SIT) proposed as a possible method of desensitization and induction of tolerance is now increasingly used to treat food allergies (Rupa and Induction of oral tolerance by deamidated gliadin Abe et al Mine, 2012;Chen et al, 1994). Several studies on this therapy have shown successful examples for specific food allergens such as wheat (Troncone and Ferduson., 1988), milk (Hachimura et al, 1993;Ueno et al 2016), egg (Chen et al, 1994;Rupa and Mine, 2012;Yamada et al, 2014), peanut (Strid et al, 2004), and beef (Tanabe et al, 2004). The currently understood mechanism of the oral-SIT is thought to be associated with the modification of cellular and humoral response to allergens.…”
Section: Introductionmentioning
confidence: 99%